a+5+7=3(4+6a)-2(7a+3)

Simple and best practice solution for a+5+7=3(4+6a)-2(7a+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for a+5+7=3(4+6a)-2(7a+3) equation:


Simplifying
a + 5 + 7 = 3(4 + 6a) + -2(7a + 3)

Reorder the terms:
5 + 7 + a = 3(4 + 6a) + -2(7a + 3)

Combine like terms: 5 + 7 = 12
12 + a = 3(4 + 6a) + -2(7a + 3)
12 + a = (4 * 3 + 6a * 3) + -2(7a + 3)
12 + a = (12 + 18a) + -2(7a + 3)

Reorder the terms:
12 + a = 12 + 18a + -2(3 + 7a)
12 + a = 12 + 18a + (3 * -2 + 7a * -2)
12 + a = 12 + 18a + (-6 + -14a)

Reorder the terms:
12 + a = 12 + -6 + 18a + -14a

Combine like terms: 12 + -6 = 6
12 + a = 6 + 18a + -14a

Combine like terms: 18a + -14a = 4a
12 + a = 6 + 4a

Solving
12 + a = 6 + 4a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-4a' to each side of the equation.
12 + a + -4a = 6 + 4a + -4a

Combine like terms: a + -4a = -3a
12 + -3a = 6 + 4a + -4a

Combine like terms: 4a + -4a = 0
12 + -3a = 6 + 0
12 + -3a = 6

Add '-12' to each side of the equation.
12 + -12 + -3a = 6 + -12

Combine like terms: 12 + -12 = 0
0 + -3a = 6 + -12
-3a = 6 + -12

Combine like terms: 6 + -12 = -6
-3a = -6

Divide each side by '-3'.
a = 2

Simplifying
a = 2

See similar equations:

| 3a+7=2x-8b | | 2x-7/4=-8 | | 4x/x-y | | 2/3y=2/9 | | 4.6+1.4n=1.52 | | 14+20=10x+2x | | (2n-8)/(n-4) | | c-4/5=-1/3 | | 2=2-11 | | 3x+xy+3y=1 | | 400=20n | | 6x+7x=26 | | 3x^3+72=-72y | | 3z/10-4=4 | | 3=-g | | 25a^3+20a^2= | | 2x^2+28x=98 | | (5+x)(8x)=1220 | | (3x-2)^(1/2)=7 | | x+128+86+72=360 | | -4=r/2 | | 1/2x-1/4y=5 | | x+104+119+61=360 | | 10y-2y+11=3+8x+-4x | | x/9-6=-6 | | z/7-6=4 | | 1-4y=7-5y | | 21+2(50)=650 | | 0.15n+0.05(4250-n)=0.07(4250) | | 45+x+99+102=360 | | -14091=0.6213x^2+468.84x | | z/7-6=14 |

Equations solver categories